'United she stand, divided she fall' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
There are many steps for ACP women to climb on the stairway to empowerment or, put simply, to enabling them to run their own lives. They include access to education and finance, and grasping the use of new information and communication...